2020
DOI: 10.3389/fimmu.2020.591571
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Phosphoglycerol Dihydroceramide Produced by Periodontal Pathogen Porphyromonas gingivalis in the Pathogenesis of Alzheimer’s Disease

Abstract: BackgroundAmong different types of sphingolipids produced by human cells, the possible engagement of ceramide species in the pathogenesis of Alzheimer’s disease (AD) has attracted recent attention. While ceramides are primarily generated by de novo synthesis in mammalian cells, only a limited number of bacterial species, produce ceramides, including phosphoglycerol dihydroceramide (PGDHC) that is produced by the key periodontal pathogen Porphyromonas gingivalis. Emerging evidence indicates that virulence facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…According to the study of Dominy et al, on mice, the presence of P. gingivalis and gingipaïn in the brain plays a central role in the pathogenesis of AD [ 39 ]. In vitro, Yamada et al demonstrated that exposure to phosphoglycerol dihydroceramide produced by P. gingivalis (PGDHC) increased Aβ peptide secretion in a dose-dependent manner in the Chinese hamster ovary-7WD10 cells, stably expressing wild-type human amyloid precursor protein (APP) and induced specific phosphorylation of Tau protein in a dose-dependent manner in human neuroblastoma cells [ 40 ]. In rats, Zhang et al showed a significant elevation of Aβ1-40 peptide levels in the cerebral cortex of AD rats with periodontitis compared to AD rats without it [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study of Dominy et al, on mice, the presence of P. gingivalis and gingipaïn in the brain plays a central role in the pathogenesis of AD [ 39 ]. In vitro, Yamada et al demonstrated that exposure to phosphoglycerol dihydroceramide produced by P. gingivalis (PGDHC) increased Aβ peptide secretion in a dose-dependent manner in the Chinese hamster ovary-7WD10 cells, stably expressing wild-type human amyloid precursor protein (APP) and induced specific phosphorylation of Tau protein in a dose-dependent manner in human neuroblastoma cells [ 40 ]. In rats, Zhang et al showed a significant elevation of Aβ1-40 peptide levels in the cerebral cortex of AD rats with periodontitis compared to AD rats without it [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…While neuroimmune interactions are essential to brain function [ 45 ], chronic inflammation appears to be a key factor in the pathophysiology and clinical progression of AD [ 46 ]. In vitro, Yamada et al showed that exposure of human neuroblastoma cells to PGDHC or Pg-LPS increased expression of the senescence-associated secretory phenotype involving β-galactosidase, cathepsin B, cysteine, and pro-inflammatory cytokines TNF-α and IL-6 [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, phosphoglycerol dihydroceramide (produced by the periodontal pathogen Porphyromonas gingivalis) promotes amyloidogenesis and hyperphosphorylation, and promotes the pathogenesis of AD (Yamada et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While it has been demonstrated that intracellular host ceramides increase LPM and directly activate CatB in the cytoplasm of myeloid cells, 23 there is no clear evidence for the association between CatB activity and PGDHC in osteoclastogenesis and osteolysis. However, we recently demonstrated that PGDHC significantly elevates the expression of CatB in neurons, in vitro 24 . Thus, these observations raise an intriguing question of whether PGDHC plays a role in CatB release into the cytosol leading to dramatically elevated RANKL‐induced osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 96%
“…However, we recently demonstrated that PGDHC significantly elevates the expression of CatB in neurons, in vitro . 24 Thus, these observations raise an intriguing question of whether PGDHC plays a role in CatB release into the cytosol leading to dramatically elevated RANKL‐induced osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%